HOSPITAL MANAGEMENT INFORMATION SYSTEM EVALUATION AT GRHA PERMATA IBU DEPOK - Yanti, Layli Hardi; Umniati, Naeli (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2024)
The GRHA Permata Ibu Hospital in Depok has been implementing the Hospital Management Information System (HMIS) since 2013 to support all hospital service processes. An evaluation of the HMIS is necessary to understand the actual state of the information system implementation. The objective is to examine and assess the HMIS at GRHA Permata Ibu Hospital to achieve results that are comparable using specific benchmarks. The goal is to obtain performance outcomes that support better, effective, and efficient services, and to identify the system's current condition for further action planning to improve its performance. The research follows a quantitative method with an online survey approach using Google Forms. The HOT-Fit evaluation model is used to assess the readiness level for utilizing an information system, focusing on the crucial components of Human, Organization, Technology, and Net Benefits. The study's results reveal that out of the 13 developed hypotheses, 6 hypotheses were accepted, while 7 hypotheses were rejected. Therefore, the research proves that not all proposed hypotheses are empirically supported. Based on the test results, several recommendations are provided to enhance the success rate of the HMIS implementation at GRHA Permata Ibu Hospital in Depok.